Development and Validation of the Brief Folate-Specific Food Frequency Questionnaire for Young Women’s Diet Assessment - Głąbska, Dominika (Int J Environ Res Public Health, 2017)
The tools enabling brief assessment of folate intake may be of great value for public health purposes. The aim of the presented study was to design a brief folate-specific food frequency questionnaire for Central and Eastern European population of women, as well as to assess the validity and reproducibility of the designed Folate-Intake Calculation-Food Frequency Questionnaire (Fol-IC-FFQ) on a group of Polish women aged 20–30 years. Participants collected 3-day dietary records and completed the Fol-IC-FFQ twice (FFQ1: directly after the dietary record; and FFQ2: six weeks later). The analysis included an assessment of validity (comparison of the results of FFQ1 and 3-day dietary record) and of reproducibility (comparison of the results of FFQ1 and FFQ2). In assessment of validity, a Bland-Altman index of 5.3% was observed. In assessment of reproducibility, a Bland-Altman index of 2.7% was observed, the share of individuals classified into the same intake adequacy category was over 85%, the share of individuals classified into the same tertile was almost 75%, the weighted κ statistic indicated substantial agreement (0.67) and correlation was significant (p = 0.0000; R = 0.7995). Assessment of the Fol-IC-FFQ revealed a satisfactory level of validity and very good level of reproducibility in the population of young Polish women. The Fol-IC-FFQ may be considered a valid tool for the assessment of folate intake in young Polish women and a promising tool for the assessment of folate intake in young women in Central and Eastern Europe.